2018
DOI: 10.1007/s40292-018-0267-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Correlates of Left Ventricular Hypertrophy in Black Africans

Abstract: In summary, blood pressure levels were the main determinants of LVH in black Africans, although different anthropometric variables showed mild influence in LVM. Our data suggests that LVH prevalence and determinants in black Africans are similar to that reported for African-Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…It has been reported that blacks are more likely to develop LVH than whites in the United States 23 . The studies on black populations living in Africa show that the overall prevalence of LVH in Gambia was 41% 24 , 62% in Cameroon 25 , and 41% in Angola 26 .Our study indicated that the prevalence of LVH in Ghana (~6%) is significantly lower than that in other African countries. Further studies with comprehensive comparison of sociodemographic and cultural factors in Ghana versus the other African countries are warranted.…”
Section: Discussionmentioning
confidence: 48%
“…It has been reported that blacks are more likely to develop LVH than whites in the United States 23 . The studies on black populations living in Africa show that the overall prevalence of LVH in Gambia was 41% 24 , 62% in Cameroon 25 , and 41% in Angola 26 .Our study indicated that the prevalence of LVH in Ghana (~6%) is significantly lower than that in other African countries. Further studies with comprehensive comparison of sociodemographic and cultural factors in Ghana versus the other African countries are warranted.…”
Section: Discussionmentioning
confidence: 48%
“…14 In the present analysis, increased LVMI was the only CV parameter that disproportionately affected African American children across both the nonglomerular and the glomerular CKD groups. Studies have previously reported higher LVMI among African Americans than other racial and ethnic groups, [15][16][17][18] as well as high prevalence of left ventricular hypertrophy (LVH) among Black individuals living in Africa, 19 however the cause is not known. It has been posited that higher rates of LVH among African Americans may be related to psychosocial stress imposed by socioeconomic disparities and perceived racism.…”
Section: Discussionmentioning
confidence: 99%
“…This was a cross-sectional study conducted among untreated hypertensives, diabetic patients and normal individuals who participated in studies that were done to determine prevalence and functional consequences of echocardiographically determined LVH at Muhimbili National Hospital in Dar es Salaam, Tanzania. 9,10,30 The present analysis include all adult (≥18 years) participants for whom an electrocardiogram was also recorded at the time of echocardiogram examination.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The existence of LVH in hypertensive, diabetic or even the general population has therefore important implications for assessing risk and for management with regards to decision making on interventions and/or medications to be used. 8 LVH has been found to be highly prevalent among hypertensive and diabetic blacks in Africa and in the USA, [9][10][11][12] which could partly explain the increased cardiovascular morbidity and mortality seen in blacks. 13,14 It is therefore especially important to accurately diagnose LVH in these populations.…”
Section: Introductionmentioning
confidence: 99%